Estudio comparativo entre eco obstétrico, medición manual de la altura del fondo uterino AFU y fecha de la última menstruación FUM en la determinación de edad gestacional en mujeres multíparas que cursan con embarazo de 12 a 36 semanas gestacionales hospitalizadas en el Área de Gineco obstetricia del Hospital Regional Isidro Ayora en el periodo enero-julio de 2014 - Encarnación Quinche, José Eliceo (2015)
This research work entitled "COMPARATIVE STUDY OF ECO OBSTETRICIAN, MANUAL MEASURING THE HEIGHT OF UTERINE FUND (AFU) AND DATE OF LAST MENSTRUAL PERIOD (LMP) IN THE DETERMINATION OF GESTATIONAL AGE IN MULTIPAROUS IN WOMEN WITH 12-36 GESTATIONAL WEEKS OF PREGNANCY WHO ARE HOSPITALIZED IN GYNECOLOGY AND OBSTETRICS AREA OF REGIONAL HOSPITAL ISIDRO AYORA "In the period from January to July 2014, It is of quantitative type with prospective cross-sectional . The sample was made to 60 patients and the objectives were to determine the differences between gestational weeks obstetrical ultrasound, fundus height and date of last menstrual period, as well as their sensitivity, found of degree the correlation between each other of these methods, taking as reference the date of last menstruation dependable. The data were processed using Excel 2010 program, the results were: the variation of age gestational between the date of last menstruation and uterine fundus height is the ± 2 weeks gestation that 60 %, while between the date of last menstruation and the valuation through obstetric ultrasound height is the ± 2 weeks gestation that 86,6 %, the sensitivity of the uterine fundus height is 60 %, in compared with the obstetric ultrasound that has 86 % in the determining of age gestational. The correlation in the determining of the age gestational between the height of fundus and obstetric ultrasound in the second trimester is the 0.78, in the third trimester is the 0.32. The correlation in the second trimester between the date of last menstruation and height of fundus is the 0.83, between the date of last menstruation and obstetric ultrasound the correlation is the 0.94 Keywords: Date of last menstruation, obstetric ultrasound, uterine fundus height, sensitivity, specificity.